Small intestinal damage associated with the use of nonsteroidal anti-inflammatory drugs - A. E. Karateev; E. V. Moroz; E. V. Kryukov (Alʹmanah Kliničeskoj Mediciny, 2019)
The use of nonsteroidal anti-inflammatory drugs (NSAID), even if short-term, may be associated to small intestinal complications, such as erosions, ulcers and chronic mucosal inflammation. Video capsule endoscopy allows for identification of such lesions in 20 to 55% of the patients who have taken nonselective NSAID for 2 to 4  weeks. The pathophysiology of NSAID-induced enteropathy is related to a reduced reparative potential of the mucosa and abnormalities of the microbial balance in the small intestine. In real world practice, NSAID enteropathy is commonly asymptomatic, and its manifestations, such as bleeding, perforation and ileus, are quite rare (about 0.3 episodes per 100  patient-years). The main manifestation of NSAID enteropathy is chronic iron deficient anemia. The use of rebamipide, sulfasalazine, mesalazine, and rifaximin has been discussed in the treatment of NSAID enteropathy, whereas its prevention implies preferential administration of coxibs, the use of rebamipide and probiotics.